Thermodynamic Considerations in the Sorption of Organic Contaminants by Soils and Sediments. 1. The Isosteric Heat Approach and Its Application to Model Inorganic Sorbents - Huang, Weilin; Weber, Walter J (Environmental science & technology, 1997)
Isosteric heats of sorption of phenanthrene from aqueous solution were determined for a hydrophobic sorbent (graphite) and for four hydrophilic sorbents (α-Al2O3 and three mesoporous silica gels). The Clausius−Clapeyron equation was used in conjunction with temperature-corrected aqueous-phase solute activity coefficients to compute isosteric heats from measured temperature-dependent Freundlich isotherm parameters. The results reveal that sorption of phenanthrene by graphite is exothermic, whereas its sorption by each of the other four model sorbents is primarily endothermic. This is consistent with the expected occurrence of distinctly different molecular interactions of solute and solvent molecules at hydrophobic and hydrophilic surfaces. Phenanthrene competes favorably with water for sorption on hydrophobic surfaces, but cannot compete effectively with water for sorption on hydrophilic surfaces; in the latter cases, the low level of sorption that does occur is driven by entropy gain by water molecules in bulk phase. This report on enthalpy relationships and molecular-level interpretation of observed sorption behavior for rigid solid sorbents is the first in a series of papers on the subject. Subsequent papers utilize the experimental approach and mechanistic information developed here to explore operative sorption mechanisms in the more complex realms of physically expandable and chemically more heterogeneous soil/sediment organic matrices.